Radiation Chemistry Provides Nanoscopic Insights into the Role of Intermediate Phases in CeO2 Mesocrystal Formation. (21st December 2021) - Li, Zhuofeng; Piankova, Diana; Yang, Yi; Kumagai, Yuta; Zschiesche, Hannes; Jonsson, Mats; Tarakina, Nadezda V.; Soroka, Inna L.
Abstract: The role of intermediate phases in CeO2 mesocrystal formation from aqueous Ce III solutions subjected to γ‐radiation was studied. Radiolytically formed hydroxyl radicals convert soluble Ce III into less soluble Ce IV . Transmission electron microscopy (TEM) and X‐ray diffraction studies of samples from different stages of the process allowed the identification of several stages in CeO2 mesocrystal evolution following the oxidation to Ce IV : (1) formation of hydrated Ce IV hydroxides, serving as intermediates in the liquid‐to‐solid phase transformation; (2) CeO2 primary particle growth inside the intermediate phase; (3) alignment of the primary particles into "pre‐mesocrystals" and subsequently to mesocrystals, guided by confinement of the amorphous intermediate phase and accompanied by the formation of "mineral bridges". Further alignment of the obtained mesocrystals into supracrystals occurs upon slow drying, making it possible to form complex hierarchical architectures. Abstract : By means of radiation chemistry, different stages of CeO2 mesocrystal formation are revealed. The nucleation and growth of the primary particles, followed by their self‐assembly into mesocrystals, occur inside a hydrated Ce IV hydroxide phase. The hydroxide forms as the initial phase and serves as an intermediate in the liquid‐to‐solid transformation. Mesocrystals can be used as buildings blocks for designing complex hierarchical structures.